Multi-site musculoskeletal pain in mine workers exposed to cold environment - Ringberg, Helge (UiT Norges arktiske universitet, 2015)
Objectives: We aimed to examine the prevalence of musculoskeletal single- and multi-site pain and exposure factors from two high north mining populations. In addition, we aimed to analyze for possible associations between perceived cold and pain in single and multiple locations. Methods: This study follows a cross sectional epidemiological design. Data was collected by questionnaire among 254 miners from two open pit mines; Stjernøya, Norway and Aitik, Sweden. Gathered was data on musculoskeletal ailments and pain during the previous month and year across 9 locations, perceived whole-body cold during damp and dry cold, and additional covariates, adjustment factors and exposures. All data presented are accompanied by tables. In addition, binary logistic regression was used to analyze any associations between musculoskeletal pain and cold exposure. Results: Feeling cool or cold was reported by 13.3% of miners during damp cold and by 34.8% during dry cold. Single-region pain was reported by 18.6%, whereas pain in two, three or four regions affected 27.7%, 24.1% and 17.0%, respectively. When adjusting for covariates we found no significant association between cold exposure and the presence of single- or multi-site pain. Conclusions: Musculoskeletal pain, both single- and multi-site, is common among miners in the Barents region. Although miners are working in the low winter temperatures, most do not feel cold. No significant association was found between cold exposure and musculoskeletal pain. Further studies should investigate the epidemiology and ramifications of multi-site pain while also considering possible effects of cold.